Een zoektocht naar de identiteit van het sociaalwerkonderzoek: een reflectie over de kenmerken van een academische discipline - Peter Raeymaeckers; Kristel Driessens; Michel Tirions (Journal of Social Intervention: Theory and Practice, 2016)
SAMENVATTINGEen zoektocht naar de identiteit van het sociaalwerkonderzoek: een reflectie over de kenmerken van een academische discipline Wat is sociaalwerkonderzoek? Verschillende auteurs stellen vast dat het sociaalwerkonderzoek zich niet makkelijk laat definiëren. Sommigen drukken de eigenheid van sociaalwerkonderzoek graag uit in termen van eclecticisme, holisme en diversiteit. Dit is niet zonder gevaar. De specifieke eigenheid van het sociaalwerkonderzoek dreigt hierdoor immers verloren te gaan. Deze bezorgdheid vormt de aanzet voor dit artikel. We schetsen de contouren van een academische discipline die door de recente internationale definitie van het sociaal werk op de voorgrond is komen te staan. Hoe gaan we te werk? We stellen vast dat we de grenzen van het sociaalwerkonderzoek niet stevig kunnen vastzetten. Het is wel mogelijk om enkele kenmerken te formuleren. Een eerste kenmerk gaat over de inhoud en betreft het terrein waarop de sociaalwerkonderzoeker zich begeeft. Een tweede behandelt de wetenschappelijke methode en een derde bekijkt de verhouding tussen theorie en praktijk. Een vierde kenmerk gaat over de gemeenschappelijke maatschappelijke bezorgdheid die eigen is aan elke sociaalwerkonderzoeker. Meer specifiek benadrukken we het belang van de bezorgdheid over sociale uitsluiting en sociale rechtvaardigheid op verschillende terreinen van het maatschappelijke leven.  ABSTRACTThe identity of social work research: reflections on an academic discipline What is social work research? Scholars agree that the search for the identity of social work research is a challenging task. Some authors express this identity in terms of holism, eclecticism or diversity. We, however, argue that when scholars embrace the diversity of social work research, social work research loses its specific identity. We therefore believe that it is crucial that social workers as well as social work academics reflect on the identity of social work research. We refer to the international definition of social work and define social work as both a profession and as an academic discipline. However, while there is a consensus on the importance of the academization of social work research, the debate on the identity of social work research is often neglected by the social work community. In the first part of this article, we review the main challenges of the process of academizing social work. We argue that social work academics must deal with specific challenges, such as confronting different voices in the debate on the role of social work, the tension between practice and theory, the fragmentation of the discipline and the consequences of the disciplinarization, because of the inherent ambiguity of social work. We then elaborate on the common features of social work research. We make a distinction between four characteristics: the terrain, the scientific method, the balance between theory and practice, and a shared concern to fight for social justice. We illustrate these characteristics with international social work research and studies from Belgium and the Netherlands.The first of these characteristics involves the content of social work research and is defined as the terrain. The first terrain is the development of social work practice and methods. Researchers working in this terrain use empirical research to investigate the everyday reality of social work practice, the effectiveness of particular practices or the problems and difficulties that social workers encounter. This type of research often results in the development and improvement of social work methods. A second terrain involves researchers who analyze clients and target groups. These scholars analyze the problematic and complex life-world of clients and target groups, their expectations of social work and how social work should take into account the needs and specific characteristics of very vulnerable target groups. Another terrain is defined as research that focuses on the context of the social worker. These scholars elaborate on the impact of social policy or changes in the welfare state on social work practice. This terrain also includes research into the organizational context of social work. Here, scholars address the question how the organizational context influences social work practice and how service organizations should be organized to accommodate the complex reality that social workers are confronted with during their everyday encounters with vulnerable target groups. Finally, the fourth terrain focuses on research that deals with the specific tensions and ambiguity in the social work profession. These studies analyze the identity of the social work profession. For example, some of these scholars analyze the unique contribution of social work when interdisciplinary partnerships with other disciplines such as psychologists, doctors or nurses are involved.The second characteristic of social work research involves methodology. Social work researchers adopt ideas from three different research paradigms: positivism, constructivism and critical realism. We define social work researchers as generalist social scientists, who practise quantitative, qualitative and critical realist analysis. However, we argue that these different paradigms often result in highly complementary perspectives and scientific findings on the everyday reality of social work. We therefore advocate the need for more mixed methods to gain a more detailed perspective on the practice of social workers.Furthermore, we also show how social work research is situated on the intersection between practice and theory. We argue that in social work research, no distinction can be made between fundamental scientific research and practice-oriented research. The findings of social work research are relevant both to the development of social work practice and to the development of scientific knowledge of social work research. Social work research must legitimize itself in the eyes of both social work practice and the scientific community. This means that social work researchers must find ways to analyze the “missing link” between theory and practice. We elaborate on the important role of implementation research that focuses on a scientific analysis of the implementation of social work methods, social work interventions or practices.Finally, this article emphasizes that social work researchers share a common concern, often expressed in terms of the fight for social justice, the eradication of poverty and the protection of the rights of the most vulnerable target groups. This means that the social work researcher tends to “take sides” when taking up a position on vulnerable target groups. We argue that the contribution of social work researchers in the public debate is based on their empirical research.In the conclusion of this article, we elaborate on the main challenges concerning the education of Master’s students in social work and social work researchers. We emphasize that social work education and social work research must maintain their specific identities, while continuing to draw on and collaborate with a range of disciplines, both in practice and in science. Our main conclusion is that social work education must embrace the diversity of social work research and, at the same time, address the social work identity of both research and practice in its curriculum. We also argue that social work researchers must address scientific readers and peers in the international academic community, but also continue their efforts in finding ways to involve social workers, service users and policy makers in their research.